DNA EXAMINATION OF SUPERIMPOSED TRACES OF BLOOD FROM A VICTIM AND EPITHELIAL CELLS FROM PERPETRATOR ON TRACE EVIDENCE - Apostolov A.; Angelova E.; Iliev P.; Odzhakov F. (Science & Research)

(untitled)
Introduction Examination of biological traces on physical evidence by the method of DNA profiling is an extremely important and reliable way to identify the perpetrators of criminal offenses. In expert practice, it is not uncommon for biological material to be deposited by the victim and the physical perpetrator of the crime. Materials and methods A case of murder of a 29-year-old woman with multiple traumas to her body is presented. In the course of the investigation, several objects with blood traces on them have been obtained. The purpose of the examination conducted by the method of DNA profiling has been to look for the presence of deposited biological material on the physical evidence from the perpetrator of the crime, applying Real-Time PCR; Quantifiler™ Trio DNA Quantification Kit; NGM Detect™ PCR Amplification Kit; Yfiler™ Plus PCR Amplification Kit. Results After the initial genotyping of the traces of blood on the objects, a mixed genetic profile of the victim and low added alleles of another male person has been established, without the possibility of deriving his genetic profile. Discussion In the presented case, due to the prevailing amount of genetic material from the victim in a mixed sample, is analyzed the possibility to use the approach for genotyping the left cellular material by the man holding the knives and golf club, using sex-defining genetic markers contained in his Ychromosome. Conclusion The use of sex-defining Y-chromosome sets of genetic markers to differentiate genetic profiles in mixed female-male biological traces allows ignoring the female component, with its predominant amount masking the deposited cellular material by the perpetrator.